1995
DOI: 10.1111/j.1365-2230.1995.tb01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Uraemic pruritus is not related to plasma histamine concentrations

Abstract: Pruritus is a common symptom in uraemic patients and its aetiology is poorly understood, although several factors have been implicated, including high histamine plasma levels. The aim of the study was to evaluate plasma levels of histamine in patients on maintenance haemodialysis in relation to the presence of itching (35 pruritic patients = group A; 50 non-pruritic patients = group B). Furthermore, we compared the values obtained with those of a healthy control group (64 subjects). We observed increased plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…Some investigators have found a positive correlation between plasma histamine levels and pruritus [7, 8, 11, 15, 16], but this has not been confirmed by others [5, 30]. In our study, the plasma histamine levels of patients with pruritus were higher than those of nonpruritic patients, but the difference was not statistically significant (p = 0.06).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Some investigators have found a positive correlation between plasma histamine levels and pruritus [7, 8, 11, 15, 16], but this has not been confirmed by others [5, 30]. In our study, the plasma histamine levels of patients with pruritus were higher than those of nonpruritic patients, but the difference was not statistically significant (p = 0.06).…”
Section: Discussioncontrasting
confidence: 45%
“…It was reported that plasma histamine levels were increased in uremic patients, mainly in those with pruritus [5, 7, 8, 11, 15, 16, 29, 30]. Some investigators have found a positive correlation between plasma histamine levels and pruritus [7, 8, 11, 15, 16], but this has not been confirmed by others [5, 30].…”
Section: Discussionmentioning
confidence: 79%
“…There is a correlation between plasma histamine levels and pruritus [52,55]. It is found that histamine levels in patients with UP is significant higher compared to nonpruritic subjects [52,55] but specific differences in plasma histamine levels in subjects with and without UP cannot be found [26,56]. Since antihistamine has been widely used but ineffective for the treatment of UP, histamine should not have a significant role for this symptom [57].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Despite the evidence for release of histamine, there was no correlation found between plasma histamine levels and severity of pruritus and antihistamines lack any activity in uremic patients suggesting that plasma histamine does not play a remarkable role in uremic pruritus [ 14 ].…”
Section: Uremic Pruritusmentioning
confidence: 99%